Backlash: Undesirable Effects of Female Economic Empowerment - Sanna Ericsson (Lund University, School of Economics and Management, Department of Economics, 2020)
This paper estimates the effect of female economic empowerment on domestic violence. I use individual level data from high-quality Swedish administrative registers on women's earnings and hospital visits relating to assault. With this third-party reported violence measure, I overcome the issue of selective under-reporting of violence. I proxy female economic empowerment with a measure of women's potential earnings, caused by local changes in female-specific labour demand. This measure reflects the outside option of the marriage, and captures earnings variation that is not endogenous to domestic violence. I show that, even while keeping the earnings of husbands constant, the causal effect of increasing women's potential earnings on domestic violence is positive and substantial. In addition, I show that increasing women's potential earnings increase the husbands' risk of destructive behaviour, such as stress, anxiety, substance abuse and assault. Taken together, these results indicate that improving women's relative economic position triggers a male backlash response, even in presumably gender-equal Sweden.
Keywords: D13; I12; J12; J16; Z13; 330; domestic violence; potential earnings; household bargaining; male backlash; local labour demand